PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL GUIDED INQUIRY UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS VIII SMP/MTs - Tiara Fikriani (JURNAL PENDIDIKAN ROKANIA, 2016)
The purpose of this study was to produce a mathematical dipembelajaran inquiry-based teaching materials for teaching linear equations in two variables topics are valid, practical and effective. By applying the model of Plomp. consists of three phases. At this stage of the assessment, obtained practicality of the implementation of the Lesson Plans, and practicality distrubuted questionnaires to teachers and students. The results showed that the mathematics-based guided inquiry was valid, practical, and effective